2002
DOI: 10.1038/sj.ejcn.1601362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-week weight-loss program on cardiovascular disease risk factors and regional body composition

Abstract: Objective: To determine the influence of weight loss on multiple cardiovascular disease (CVD) risk factors. Design: Overweight women (n ¼ 12; mean 44.2% fat) and men (n ¼ 10; mean 30.7% fat) participated in an 8 week weight-loss program that included dietary, exercise, multi-vitamin=mineral supplementation, and behavior modification components. Measurement of total and regional body composition assessed using dual energy X-ray absorptiometry (DEXA), circumferences and blood sampling for total cholesterol, LDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
33
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 41 publications
11
33
0
2
Order By: Relevance
“…conducted in a parallel design, a study on 106 obese men and women with type 2 diabetes who were randomized to a prescriptive 16-week caloric restricted diet (6,000-7,000 kJ/day), with supervised resistance exercise training (n = 65) or without supervised resistance exercise training (n = 41) (three times per week) and found that structured caloric restricted diet with or without resistance exercise training improves body weight, glycated hemoglobin, diabetes-specific emotional distress and quality of life questionnaire in overweight and obese patients with type 2 diabetes Our results revealed that BMI and serum leptin were significantly decreased upon weight loss among obese type 2 diabetes patients. Our findings were consistent with Sartorio and colleagues who proved that the circulating levels of leptin have been shown to decrease in response to decreases in energy availability 42 , also Volek and colleagues suggested that significant decreases in leptin occur as part of an 8-week weight loss program 43 , which similarly occurred in the present study.…”
supporting
confidence: 82%
“…conducted in a parallel design, a study on 106 obese men and women with type 2 diabetes who were randomized to a prescriptive 16-week caloric restricted diet (6,000-7,000 kJ/day), with supervised resistance exercise training (n = 65) or without supervised resistance exercise training (n = 41) (three times per week) and found that structured caloric restricted diet with or without resistance exercise training improves body weight, glycated hemoglobin, diabetes-specific emotional distress and quality of life questionnaire in overweight and obese patients with type 2 diabetes Our results revealed that BMI and serum leptin were significantly decreased upon weight loss among obese type 2 diabetes patients. Our findings were consistent with Sartorio and colleagues who proved that the circulating levels of leptin have been shown to decrease in response to decreases in energy availability 42 , also Volek and colleagues suggested that significant decreases in leptin occur as part of an 8-week weight loss program 43 , which similarly occurred in the present study.…”
supporting
confidence: 82%
“…Similarly, Volek et al 43 did not observe changes in homocysteine after 4 kg of weight loss on a reduced fat diet, with vitamin/mineral supplements including folic acid. Similarly, Fleming 44 in a study of 100 men and women, found no significant effect of weight loss in homocysteine.…”
Section: Homocysteine and Folatementioning
confidence: 90%
“…In addition, weight loss could reduce insulin hypersecretion and increase insulin sensitivity and b-cell function, 34 and decrease blood pressure, and thus, improve hyperlipedemia 35 and hypertension.…”
Section: Discussionmentioning
confidence: 99%